ROLE OF NEP 2020 AT THE FUNDAMENTAL AND PREPARATORY STAGES OF LANGUAGE LEARNING - S. D. Selvasundari (International Journal of Research -GRANTHAALAYAH, 2026)
The National policy of Education 2020 insists the significance of language in shaping the educational landscape of India, particularly in elementary and preparatory education. This policy encourages the use of mother tongue or regional languages as the medium of instruction, aiming to develop cognitive skills, cultural preservation and inclusive. By adopting a multilingual approach, NEP 2020 seeks a connect the gap between home and school languages, enhancing students’ learning experiences and academic performances. This article explores the role of language in NEP 2020, highlighting its potential benefits, challenges and implications foe elementary and preparatory education in India. The analysis highlights the importance of effective implementation, resource allocation and teacher training to ensure the success of multilingual education initiatives. Ultimately, NEP 2020’s language provisions have the potential to change India’s educational system, promoting linguistic diversity, equity and quality education for all.